2008
DOI: 10.1371/journal.pone.0002429
|View full text |Cite
|
Sign up to set email alerts
|

From Offshore to Onshore: Multiple Origins of Shallow-Water Corals from Deep-Sea Ancestors

Abstract: Shallow-water tropical reefs and the deep sea represent the two most diverse marine environments. Understanding the origin and diversification of this biodiversity is a major quest in ecology and evolution. The most prominent and well-supported explanation, articulated since the first explorations of the deep sea, holds that benthic marine fauna originated in shallow, onshore environments, and diversified into deeper waters. In contrast, evidence that groups of marine organisms originated in the deep sea is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
115
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 39 publications
12
115
0
2
Order By: Relevance
“…Goldberg et al 2005). The present study adds to the growing body of evidence that modern shallow-water environments are not exclusively the result of in situ evolution but received considerable input from deep-sea invaders (Lindner et al 2008). Although, admittedly, adding the vertical migration component presents the risk of making palaeobiodiversity analyses exceedingly complex, straightforward exclusion of the potential contribution of deep-sea environments to shallow-water diversity is an oversimplification that is no longer tenable.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Goldberg et al 2005). The present study adds to the growing body of evidence that modern shallow-water environments are not exclusively the result of in situ evolution but received considerable input from deep-sea invaders (Lindner et al 2008). Although, admittedly, adding the vertical migration component presents the risk of making palaeobiodiversity analyses exceedingly complex, straightforward exclusion of the potential contribution of deep-sea environments to shallow-water diversity is an oversimplification that is no longer tenable.…”
Section: Discussionmentioning
confidence: 82%
“…One of the very few authors to cast a comparably critical light on the shallow-water fossil record of an extant deep-sea group was Vörös (2005), who speculated that post-Palaeozoic smooth brachiopods invaded shallow environments as offshoots of stable deep-sea communities in times of suitable palaeoceanographic conditions. The potential of deep-sea groups to contribute to shallow-water diversity has recently been demonstrated by Lindner et al (2008), who showed that Recent shallow-water stylasterid corals evolved from deep-sea ancestors at least three times. Similar trends may thus be expected in other groups with both shallow and deep representatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corals are best known from shallow tropical seas, despite 465% of recorded coral species occurring below 50 m depth (Cairns, 2007;Lindner et al, 2008;Roberts et al, 2009). In contrast to their shallow-water counterparts, cold-water corals do not require light or high temperatures to survive in deep-waters because they do not have a symbiotic relationship with zooxanthellae (algae).…”
Section: Introductionmentioning
confidence: 99%